Disseminated Tuberculosis with Involvement of Appendix, Peritoneum and Right Knee Joint - A Case Report - Islam, Mohammad Syedul; Azad, Md. Abul Kalam; Mohammad, Hanif; Islam, Mohammad Mushahidul; Rahim, Md. Abdur (Journal of Medicine, 2014)
A 27 year old male presented with painful swelling of right knee joint for the last 6 months. Initially it was diagnosed as a case of reactive arthritis and was treated with NSAID with intraarticular steroids without significant improvement. Two months after the initial episode he again developed painful swelling of the right knee joint with severe abdominal pain and high grade fever. There was an ill defined ovoid mass in the right iliac fossa with generalized tenderness. ESR was raised and the ultrasonography revealed loculated ascites with appendicular lump. CT scan of the whole abdomen showed appendicular lump. FNAC from the lump showed tuberculosis. Joint fluid aspiration showed neutrophilic leucocytosis with the Total count 50,000/cmm. AFB was not found. So septic arthritis was diagnosed, but as the patient was not improving we send the patient to orthopedic department for synovial biopsy but they refused as it was septic. So a diagnosis of disseminated Tuberculosis was made with the involvement of right knee joint, appendix and peritoneum. He was put on anti TB and well responded. DOI: http://dx.doi.org/10.3329/jom.v15i2.20702 J MEDICINE 2014; 15 : 153-155